Influence of Students' Motivation on Academic Achievement Among Undergraduate Students in Malaysia - Norsuhaily, Abu Bakar; Alsmadi, Mohammad Shaban; Zuraina, Ali; Shuaibu, Auwallu; Mohd Hamidi, Solahudin (JPSP, 2022)
Motivation is essential for students to study and enhance their academic performance. This study aimed to assess the impact of student motivation on academic accomplishment among undergraduate students in the University Sultan Zainal Abidin, Malaysia. How pupils build motivation in themselves may influence how successful they are academically. Pilot research was conducted on 144 participants using exploratory factor analysis to establish the instrument's reliability and validity. However, the study showed no significant difference in accomplishment motivation between high and poor achievers. Similarly, the data found that males and females differed significantly in achievement desire. Using the Statistics Program for Social Science (SPSS) version 20, the data were analysed using correlation analysis and fundamental linear regression analysis. The findings revealed that students' motivation boosted their academic success. Similarly, the regression analysis revealed that motivation was a strong predictor of greater academic accomplishment (GPA).